Maori in governance: The voices of Maori trustees - Turner, Martin (Massey University, 2006)
While the education reforms of 1989 promised much for Maori in education, Maori membership on Boards of Trustees continues to be disproportionately low against that of non-Maori members. The governance role is significant in influencing the provision and outcomes of education for Maori students, but there has been little research into the experiences of Maori in school governance, or the factors that impact on successful partnerships between Maori and Pakeha on school boards. This research project presents the governance stories of six Maori trustees from different mainstream primary schools. With reference to the Treaty of Waitangi, it explores Maori and Pakeha conceptions of partnership, and discusses the effectiveness of the education reforms in promoting and sustaining partnership with Maori at school governance level. Through interviews conducted as part of this research, Maori trustees' understandings of their role in governance, the board's obligations to the Treaty of Waitangi, and the expectations placed on them as Maori by the board, and by their own Maori community, are explored. This project highlights some of the complex issues Maori trustees face within a governance structure which is incongruous with traditional Maori principles of collectivism, and illuminates the duality of role many Maori negotiate as school trustees.
Keywords: Maori; Education reforms; Fields of Research::330000 Education::330100 Education Studies::330104 Educational policy, administration and management